Pengaruh Etika Profesi Akuntan Publik terhadap Independensi dalam Kasus Manipulasi Laporan Keuangan PT Garuda Indonesia Tbk Tahun 2018 - Faradiba, Firstya Trista; Sodikin, Alvino Oktavierdinand; Sandari, Tries Ellia (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The 2018 financial statement manipulation case of PT Garuda Indonesia Tbk revealed a violation of the ethical principles of the public accountant profession and weak auditor independence in detecting irregularities in revenue recognition. This incident has created an urgency to empirically test the extent to which professional ethics influence auditor independence in preventing financial statement manipulation. This study aims to analyze the influence of public accountant professional ethics on auditor independence using quantitative research methods. Data were obtained through variable measurements using structured instruments which were then processed and analyzed using the SPSS application through validity tests, reliability tests, simple linear regression analysis, and t-tests to determine the significance of the influence between variables. The results of the study indicate that professional ethics has a positive and significant influence on auditor independence, where the stronger the application of ethical principles, the higher the level of auditor independence in carrying out their professional duties. The conclusion of this study confirms that the consistent application of professional ethics is a fundamental factor in maintaining auditor objectivity and preventing the recurrence of financial statement manipulation cases such as those that occurred at PT Garuda Indonesia Tbk.